Vedic Cosmology and Ethics Selected Studies - Dory Heilijgers, Henk W. Bodewitz; Houben, Jan; van Kooij, Karel (Gonda Indological Studies, 2019)
The articles by Henk Bodewitz collected in this volume, published between 1969 and 2013, deal with Vedic cosmology and ethics on basis of a systematic philological study of early Vedic texts, from the Ṛgveda to various Brāhmaṇas, Āraṇyakas and Upaniṣads. Readership: Students and specialists in Vedic studies, Religious studies, South Asian studies, Indo-European languages and History of Religions.